Insight into the adsorptive removal of Cr(VI) ions and 4-chlorophenol from aqueous media on cationic surfactant-modified cucumber peels - Sengul Tugba Ozeken; Duygu Ozdes; Celal Duran (Journal of Analytical Science and Technology, 2025)
Abstract A new and cost-effective adsorbent material was developed by chemical modification of cucumber peels (CP) with a cationic surfactant, cetyltrimethylammonium bromide (CTAB). The adsorptive behavior of CTAB-modified cucumber peels (CMCP) was investigated in the retention of an organic pollutant (4-chlorophenol) and an inorganic pollutant (Cr(VI)) through batch experiments. The adsorbents were characterized by Fourier transform infrared spectroscopy (FTIR) analysis and scanning electron microscopy (SEM) technique. Influences of initial concentrations of both pollutants, dosage of CMCP, initial solution pH, contact time, and foreign ions were parameters used to specify the optimized conditions. Results of the experiments were evaluated by three kinetic models, namely pseudo-first-order, pseudo-second-order, and intraparticle diffusion models, to find out the dominant mechanisms in the retention of 4-chlorophenol and Cr(VI). Langmuir, Freundlich, and Dubinin–Radushkevich isotherm models were applied to the adsorption data to estimate the adsorption capacity of CMCP and to describe the interactions between the species. Langmuir isotherm model fitted the data well, and the maximum Cr(VI) and 4-chlorophenol adsorption capacities of CMCP were 84.03 mg g−1 and 107.5 mg g−1, respectively. Consequently, CMCP demonstrated outstanding performance in the adsorption of both inorganic and organic pollutants, offering a low-cost, easily prepared alternative to other adsorbents reported in the literature. Graphical abstract